Population Aging and Migration - Panu Poutvaara (Institute of Labor Economics (IZA), 2021)
International migration flows largely reflect demographic patterns and economic opportunities. Migration flows increase in expected income and other pull factors in potential destinations, and in push factors in the origin, like high unemployment, low wages, and high population growth. Migration flows decrease in the geographic and cultural distance between the potential origin and destination, and in other migration costs. To the extent that migrants are employed, immigration can alleviate challenges arising from population aging. For origin countries, the effects of migration may go either way, depending on whether increased incentives to invest in education are sufficient to compensate the loss of skilled workers. Throughout the 20th century, Northern America and Australia and New Zealand attracted highest immigration flows. Latin America was consistently a continent of emigration. Europe went through a major reversal from a continent of emigration until 1950s to a continent of immigration. In the 21st century, crucial questions for demographic and migration research are how fertility rate and emigration rate are going to develop in Africa. Even modest increases in emigration from Africa would generate major increases in immigration pressure in the rest of the world, mostly in Europe. Other major questions on the future research agenda are the effects of the climate change and rapid improvements in information technology.
Keywords: F22; O15; J11; J13; J61; 330; international migration; population aging; demographic trends; fertility; immigrant workers